Corporate governance and firms in financial distress: evidence from a Middle Eastern country. (30th March 2012) - Salloum, Charbel; Azoury, Nehme
The objective of this paper is to determine the managerial governance characteristics related to financially distress companies. The failure of boards to accomplish their monitoring duties seemed to be one of the main reasons behind the actual financial distress and bankruptcy that swept companies across the planet. Through the analysis of a sample of 178 Lebanese non–listed and family owned firms, the results showed that the boards (that have a higher proportion of outside directors) are less inclined to face financial distress than the boards with a lower proportion. In addition, a different conclusion proves that the board's size and financial distress are directly linked. The paper highlights the extent to which financial distress is associated with corporate governance from a Euro Mediterranean country. It would be a source of education to Lebanese investors, who excessively go for short–term returns, and of help to regulatory authorities in the framework of making policies on corporate governance reformation.